2019
DOI: 10.1002/erv.2663
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological signature of intimacy in anorexia nervosa

Abstract: Background Intimacy and psychosexual development represent core problems of anorexia nervosa (AN). Experiential and neurobiological evidence however is scarce. Material and methods Thirty‐one female AN patients were compared with 35 non‐patients (NP) and 22 recovered participants (REC) by using functional magnetic resonance imaging. Participants viewed pictures of couples in intimate relationships and control stimuli. Results AN patients experienced intimate stimuli with lower valence and dominance. AN showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
1
10
1
Order By: Relevance
“…These results suggest the presence of dysfunctional self-evaluative processes and reduced perceptions of social rewards, and finally, they highlight the importance of brain reward networks for pathological behaviors in patients with AN. Consistent with the frequently observed disturbances in interpersonal relationships in patients with AN [93], Maier and colleagues [94] found that both patients with AN and participants who had recovered from AN display decreased activation in the superior parietal cortex and a reduced responsivity in the dorsolateral prefrontal cortex when viewing pictures displaying intimate situations. Similarly, Miyake and colleagues [95] observed a negative relationship between alexithymia, or the inability to articulate and interpret emotional experiences, and activation of the amygdala and posterior and anterior cingulate cortices during the processing of negative interpersonal words.…”
Section: Emotional Processingsupporting
confidence: 59%
“…These results suggest the presence of dysfunctional self-evaluative processes and reduced perceptions of social rewards, and finally, they highlight the importance of brain reward networks for pathological behaviors in patients with AN. Consistent with the frequently observed disturbances in interpersonal relationships in patients with AN [93], Maier and colleagues [94] found that both patients with AN and participants who had recovered from AN display decreased activation in the superior parietal cortex and a reduced responsivity in the dorsolateral prefrontal cortex when viewing pictures displaying intimate situations. Similarly, Miyake and colleagues [95] observed a negative relationship between alexithymia, or the inability to articulate and interpret emotional experiences, and activation of the amygdala and posterior and anterior cingulate cortices during the processing of negative interpersonal words.…”
Section: Emotional Processingsupporting
confidence: 59%
“…This study was part of a multimodal MRI study, which assessed structural, metabolic and other functional data [see, e.g., (31)(32)(33)(34)(35)(36)]. We replicated the aforementioned food paradigm with 31 AN and 27 NP.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, other fMRI data were gathered before the food paradigm, which was not the case in the initial study. In the current study, we used the manikins of the International Affective Picture System ( 47 ) assessing the emotional response to the visual stimuli after scanning (outside the scanner) in three dimensions (arousal, valence, dominance), as we used this approach with another paradigm ( 32 ) as part of the multimodal study. In the previous study the Likert scale was applied.…”
Section: Methodsmentioning
confidence: 99%
“…A recent review [14] suggests an alternative explanation: ED individuals can recognize others’ basic emotions, but they lose this skill when emotions become more complex and are expressed within a relationship. Relevant to this kind of hypothesis, a dysfunctional middle prefrontal cortex (MPFC) activation has been reported for processing of visual stimuli depicting couples in intimate relationships in acute and recovered AN, pointing to a state-independent alteration of MPFC activation [45,46]. Additionally, the significantly elevated alexithymia scores in both clinical groups may be also associated with MPFC dysfunction, as this is an important hub for the interhemispheric integration and transfer [47].…”
Section: Discussionmentioning
confidence: 99%